2010
DOI: 10.1590/s0066-782x2010000100011
|View full text |Cite
|
Sign up to set email alerts
|

Remodelamento cardíaco: análise seriada e índices de detecção precoce de disfunção ventricular

Abstract: Background: Supravalvar aortic stenosis (SVAS) is used to study overload-induced cardiac remodeling (CR). In this model, neither CR behavior since beginning stage nor the best parameters to identify ventricular dysfunction are clearly stated.Objective: ) Characterizing, early and evolutively, morphological and functional modifications during CR in rats with SVAS and ) identifying the most sensitive index for detecting the moment when the diastolic and systolic dysfunction first appeared in the left ventricle (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 33 publications
2
9
0
1
Order By: Relevance
“…These results are similar to those observed in animals with supravalvular aortic stenosis [58]. The increase in the A wave probably culminates in a higher velocity of transmitral flow during the end diastole.…”
Section: Discussionsupporting
confidence: 89%
“…These results are similar to those observed in animals with supravalvular aortic stenosis [58]. The increase in the A wave probably culminates in a higher velocity of transmitral flow during the end diastole.…”
Section: Discussionsupporting
confidence: 89%
“…The supravalvular AoS model is well established in scientific literature as a left ventricle (LV) hypertrophy promoter (3,4,1924). It is defined by an initial light overload followed by a slow progression, proportional to the animal's growth.…”
Section: Methodsmentioning
confidence: 99%
“…All rats were submitted to echocardiographic evaluation 6 weeks after surgery, since previous studies have shown a diastolic dysfunction and improved systolic function progression from 2 to 6 weeks (3). A commercially available echocardiograph (General Electric Medical Systems, Vivid S6, Israel) equipped with a 5-11.5 MHz multi-frequency probe, was employed as previously described (26 29).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aortic stenosis was induced according to a previously described method 4 - 7 . The three- to four-week-old animals, weighing 70-90 g, underwent anesthesia with the association of ketamine chloride (60 mg/kg) and xylidine chloride (10 mg/kg), by intraperitoneal (ip) route.…”
Section: Methodsmentioning
confidence: 99%